Bilevel Prioritization within the Energy Transition Framework for Diversified Portfolios of Green Hydrogen Production for Export - Aristizábal Cataño, Maria Camila; Orejuela Cabrera, Juan Pablo; Manotas Duque, Diego Fernando (International Journal of Energy Economics and Policy, 2025)
Green hydrogen has been proposed as an alternative to incorporate into energy portfolios and as an export product to address the economic and social challenges derived from the energy transition, especially in hydrocarbon-exporting countries; however, this energy carrier faces economic challenges associated with the cost of electricity used in its production process. This research aimed to prioritize renewable generation portfolios within the framework of an energy transition, considering attributes related to export, sustainability, and source diversity, to ensure supply continuity and reduce dependency in green hydrogen production for export. To achieve this, bilevel multicriteria analysis and an unsupervised classification algorithm were employed, based on a set of electrical projects. The results obtained highlight the importance of evaluating indicators at both project and portfolio levels in a differentiated manner, paying special attention to diversity as an essential criterion. Through the development of analysis threads, it was identified that robustness does not necessarily imply greater diversity; in this sense, in addition to scenarios with variation in criteria weights, it was necessary to construct source participation scenarios that would directly influence diversity.